Prenatal exposure to methadone or buprenorphine alters µ‐opioid receptor binding and downstream signaling in the rat brain. Issue 5 (29th June 2020) - Kongstorp, Mette; Bogen, Inger Lise; Steinsland, Synne; Nerem, Elisabeth; Salih, Triske Woshyar; Stiris, Tom; Andersen, Jannike Mørch
Abstract: There is a growing concern related to the use of opioid maintenance treatment during pregnancy. Studies in both humans and animals have reported reduced cognitive functioning in offspring prenatally exposed to methadone or buprenorphine; however, little is known about the neurobiological mechanisms underlying these impairments. To reveal possible neurobiological effects of such in utero exposure, we examined brain tissue from methadone‐ and buprenorphine‐exposed rat offspring previously shown to display impaired learning and memory. We studied µ‐opioid receptor (MOR) and N‐methyl‐D‐aspartate receptor (NMDAR) binding in the rat offspring cerebrum during development and in the hippocampus at young adulthood. Moreover, we examined activation of the Ca 2+ /calmodulin‐dependent protein kinase II (CaMKII) and the extracellular signal‐regulated kinase (ERK), which are central in the downstream signaling of these receptors. The methadone‐ and buprenorphine‐exposed rat pups displayed reduced MOR binding up to two weeks after birth, whereas the NMDAR binding was unaffected. Prenatal exposure to methadone or buprenorphine also resulted in decreased activation of CaMKII and/or ERK during development, while young adult offspring displayed increased hippocampal ERK activation. In conclusion, our findings suggest that prenatal exposure to exogenous opioids, such as methadone or buprenorphine, may disturb the endogenous opioid system during development, with long‐term effects on proteins important for cognitive functioning. Abstract : In the present study, we examined MOR binding and activation of downstream signaling proteins in brain tissue from methadone‐ and buprenorphine‐exposed rat offspring previously shown to display impaired learning and memory. Prenatal exposure to methadone or buprenorphine reduced cerebral MOR binding in rat pups for up to two weeks after birth. No change was revealed in young adult offspring. The opioid‐exposed pups also showed decreased activation of the downstream signaling proteins CaMKII and ERK, while young adults showed increased ERK activation in the hippocampus.